Postharvest physiology and molecular characterization of ethylene related genes in pollinated Dendrobium pompadour / Zuliana Razali - Razali, Zuliana (2012)
Pollination-induced senescence in Dendrobium Pompadour flowers was investigated. Pollinated flowers were held in distilled water and in treatment solutions containing either sucrose, glucose, aminooxyacetic acid (AOA) or silver thiosulphate (STS) while unpollinated flowers were held in distilled water. Morphological changes were observed visually while physiological parameters investigated included ethylene production, colour change, petal thickness, fresh weight, dry weight and water uptake. Biochemical changes determined were starch, total sugar and reducing sugar, cell wall hydrolases, total protein, soluble and insoluble protein. Furthermore, 1D SDS PAGE was also carried out to profile the protein changes in all the flowers. Finally five genes; 1-aminocyclopropane-1-carboxylate oxidase (ACCO), 1-aminocyclopropane-1-carboxylate synthase (ACCS), ethylene receptor 1 (ETR1), ethylene response sensor 1 (ERS1) and ethylene response sensor 2 (ERS2) were isolated and amplified via RT-PCR. Characterization of the isolated genes was carried out using a number of bioinformatic tools. Pollinated flowers held in distilled water demonstrated accelerated senescence which was categorized into five different stages from the point where the flower was fresh and open to reaching full closure (termination of vase life) and finally showing the first sign of necrosis (advanced stage of senescence). The morphological changes corresponded to a climacteric pattern of ethylene production with an ethylene peak detected on the day. In contrast ethylene was not detected in unpollinated flowers. Vase life of pollinated flowers held in distilled water was terminated on the 2nd day and reached advanced stage of senescence on the 7th day. Unpollinated flowers stayed fresh throughout the experiment as well as pollinated flowers held in 0.05 mM AOA and 0.6 mM STS. Vase life of flowers held in sugars was terminated on the 4th day. Accelerated physiological iii changes were also observed in pollinated flowers whereas treated flowers demonstrated a delay in the changes. Flowers held in 0.05 mM AOA and 0.6 mM STS showed similar trends of physiological changed with that of unpollinated flowers. Carbohydrate changes in pollinated flowers held in distilled water included a decline in starch and non-reducing sugars and an increase in total and reducing sugars. In unpollinated flowers and pollinated flowers held in 0.05 mM AOA and 0.6 mM STS, starch was retained while little change was observed in the status of sugars. Similar trends were observed in pollinated flowers held in 2% sucrose and 4% glucose at the initial days of observation but subsequently emulated the trend displayed by pollinated flowers held in distilled water. Measurement of cell wall hydrolases on PG, PL, PME and cellulose showed a more pronounced role for PG, PL and cellulose during pollination-induced senescence. The rate of activity for these hydrolases increased upon pollination whereas PME activity was rather low. Membrane deterioration determined by measuring electrolyte leakage was also accelerated by pollination and was found to be delayed in pollinated flowers held in treatment solutions. Total protein content in pollinated, unpollinated and treated pollinated D. Pompadour flowers exhibited a general trend of decline towards the end of the experiment. However, pollinated flowers held in distilled water showed a more rapid decline and recorded the lowest amount of total protein at the end of the experiment. Profile analysis using 1D SDS PAGE showed that three polypeptides were regulated throughout the process, which was identified as PR-like protein, SAM synthase and seed storage protein. Amongst the three proteins, the most abundant protein expressed was the PR-like protein followed by SAM synthase and the seed storage protein. The PR-like protein and SAM synthase significantly increased following pollination. All physiological parameters investigated indicated that pollination induced a series of deteriorative processes that ultimately results in the death of the perianth. The effectiveness of ethylene inhibitors in circumventing the pollination effects established the major role of ethylene in regulating the post-pollination symptoms. The inability of sugars to overcome the pollination affects as effective as ethylene inhibitors suggests that sugars may play a role secondary to that of ethylene. Finally, the ACCO and ACCS genes isolated from pollinated flowers were comparable to the genes deposited in the GenBank in terms of size and contains the signature domains that are pivotal for the genes to function. Partial sequences were obtained for ETR1, ERS1 and ERS2. Nevertheless, they contain the signature domain of ethylene receptors. All genes isolated showed strong homology to the corresponding gene family in the database. Three dimensional (3D) structure of the genes was also predicted and phylogenetic trees were constructed to show the relationship of the genes with other orchids or flowers. These are the first genes to be isolated in D. Pompadour and will be deposited into the GenBank.